Technology for Improving Distribution Network Disaster-Prevention Capabilities for Intercurrent Natural Disasters Areas Under Extreme Weather： Review and Prospect - CHEN Bin, LIAO Jinlin (Dianli jianshe)
China is particularly susceptible to natural disasters. The frequent occurrence of natural disasters under extreme weather conditions poses a significant threat to the safe operation of distribution systems. In the construction of novel distribution systems，the scope of affected objects is expanded，disaster-causing mechanisms are complex，and power-supply support is diversified. Distribution networks in multiple superimposed disaster areas must be able to prevent，sense，resist，and recover from extreme natural disasters. This study considers distribution networks as the object，as well as expounds on the concept of multiple superimposed disaster areas and the geographical distribution of distribution networks in multiple superimposed disaster areas in China. Additionally，three aspects are discussed comprehensively： disaster mechanism and simulation technology of distribution networks in multiple disaster-superimposed areas，disaster-prevention planning and design technology，and disaster-prevention operation and power-restoration technology. To enhance long-term intrinsic disaster-prevention capabilities and satisfy the short-term emergency power-supply demands of distribution networks，technological research trends to improve the disaster-prevention capabilities of distribution networks in multiple superimposed disaster areas are summarized. References for the construction of novel distribution systems and the improvement of disaster-prevention capabilities are provided.